2017
DOI: 10.3389/fgene.2017.00163
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of MicroRNAs in the Goat (Capra hircus) Rumen during Embryonic Development

Abstract: The rumen is an important digestive organ in ruminants. Numerous regulatory factors including microRNAs (miRNAs) are involved in embryonic organ development. In the present study, miRNAs expressed in the rumens of goats (Capra hircus) and their potential roles in the pathways involved in rumen development were identified using high-throughput sequencing. Histological morphology revealed a distinct difference in each layer of rumen during the period from embryonic day 60 (E60) to embryonic day 135 (E135). We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…1a). We previously reported that miRNAs expression in embryonic rumens and less number of DEMs (22 up-regulated and 20 down-regulated) was identi ed between E60 and E135 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). We previously reported that miRNAs expression in embryonic rumens and less number of DEMs (22 up-regulated and 20 down-regulated) was identi ed between E60 and E135 [18].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the expression pro le of rumen miRNAs was revealed in the two embryonic stages (E60 and E135) [18]. Here, we investigated the DEMs identi ed in the pre-weaning and post-weaning stages (D30 and D150) and rejoined analyzed the RNA sequencing data.…”
Section: Introductionmentioning
confidence: 98%
“…Goat kids were weaned at D60. The pre-natal samples were collected by cesarean section [17], while the post-natal rumens were dissected and frozen in liquid nitrogen immediately after slaughter, and then stored at −80 ‱ C. All experiments involving animals were conducted according to the Regulations for the Administration of Affairs Concerning Experimental Animals (Ministry of Science and Technology, China, revised in June 2004).…”
Section: Experimental Animals and Rumen Tissue Collectionmentioning
confidence: 99%
“…Two datasets including the newly obtained raw data (D30 and D150) and our previous data (E60 and E135) [17] were jointly analyzed in the present study. The procedures of miRNA identification and expression were performed according to the methods [17,23]. Differential miRNA expression was analyzed using the DESeq R package.…”
Section: Mirnas Data Analyses and Qpcr Validationmentioning
confidence: 99%
See 1 more Smart Citation